Wissenschafterinnen in und aus Österreich Leben - Werk - Wirken - Keintzel, Brigitta (2002)
In the present bio - bibliographic collection the life and work of female scientists, working in Austria or being originally from Austria, have been the center of research. The temporal focus extends primarily from the turn of the century to the post-war period. The first generation of female scientists at the Universities of Vienna, Graz and Innsbruck were explored. The first generation of women who achieved a habilitation in Austria, as well as the first female lecturers and professors were collected in their completeness. Those "classical" science careers can be compared with those of men. However, a detailed consideration was also given to the non- academic area. From a total of 331 lexicon articles about one-third is dedicated to the medical, psychological and therapeutic field. Due to the historical turning points of the two world wars persecution, flight, emigration and also re-migration of the female scientists move into the focus of numerous of the individual biographies. The question of similarities and differences, according to different living conditions and opportunities to those who remained in Austria, is obvious. Beyond the individual biographical aspect, a historic impression about cultural and political trends and their impact on scientific research and teaching is provided. Especially from a feminist perspective, the lexicon is a desideratum, as it is the first time that in Austria the participation of women in the production and placement of science during the considered period got comprehensively researched and documented.